PENGARUH TINGKAT PENDAPATAN KELUARGA DAN ASUPAN MAKANAN TERHADAP STATUS GIZI ANAK TAMAN KANAK- KANAK - Efy Loberta Tondang (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2017)
The objectives of the study were to determine (1) the influence of family income and food intake on the nutritional status of children, (2) family income level on nutritional status of children, (3) food intake on child nutritional status, (4) description of income level of family, and nutritional status. The type of research is ex-post facto. Sampling using propotional random sampling. Data collection methods are questionnaire, anthropometry, food recall and food frequency. Instruments tested for validity and reliability. Data analysis using descriptive and correlational analysis. The result of research showed that positive and significant effect of income and food intake on child nutritional status, Freg = 6,053> Ftabel = 3,17, (2) family income level to child nutrition status, rcount 0,288> rtabel = 0,259, (3) food intake on nutritional status, rcount = 0,324> rtabel = 0,259; (4) The level of family income, food intake, and nutritional status in sufficient category.Keywords: income level, food intake, nutritional status.